Bibliometrics study of the cancer research in the faculties of medicine and dentistry during Syrian crisis - Marwan Al-Raeei; M Osama Al-Jabban; Chadi Azmeh; Amr Al-Raeei (Oral Oncology Reports)
Background: The publishing of scientific papers is a significant role for any institution, where the scientific papers reflect the scientific research outputs of the institution or its faculties. In some institutions, there are specific focusing on specific subject areas rather than others, and in this case, these areas support the whole institution. As specific case, the cancer researchers are very significant for multiple reasons such as the sustainable development goal-3 and the health in the country. Material and methods: In this study, we analyse the output of the scientific researches of the publishing of cancer researches in medicine, and dentistry in one of the developing countries which is Syrian Arab republic. Based on the Scopus database, we discuss the effects of the scientific researches production of the Faculty of Medicine, and Faculty of Dentistry in the biggest institution of the Syrian institutions. We focus on the cancer published documents which are abstracted an indexed in Scopus database. Results: We collect the published documents, which abstracted and indexed in Scopus, for the study of scientific researches production by the Syrian researchers affiliated with Damascus University in medicine and dentistry. Mainly, we focus on the period from 2011 to 2021 which represents the main Syrian crisis time. We find the effects of the cancer researcher which are published in the journals indexed in Scopus database. Conclusion: For the main output about the cancer researchers in Damascus University, we find that more than 87% of the published documents about the cancer during Syrian Crisis are of full-length article type. Also, we find that the cancer researches published by the authors from Damascus University which are abstracted and indexed in Scopus database increased from twelve published research only to reach to 70 published research in 2021, and the same number for 2022 which reflects the developing of the cancer researches in Damascus University during the last two years. Some of the published researches are related to the biomarkers which have significant output. We found that medicine and dentistry have main role in the ranking of the related faculties and the whole institution.